Time to spent on high tech gadgets and self esteem among the students of College of Science and Computer Studies in De La Salle University-Dasmarinas. - Fresco, Ma. Corina E. (2014)
The study aims to examine the hours that an individual spent on a high-tech gadget and determine the level of self-esteem. The researchers used descriptive correlational method to calculate the data gathered from surveys, post interview and Pearson’s r results. There were 333 target population but 147 respondents were officially included in the study. The computed Pearson r was r = -0.05125 this implies a no positive relationship between time spent on hightech gadget and levels of self-esteem. However, the results from post-interview was opposite from the statistical data. The researchers believed that the participants were affected but not aware of what the conditions were occurring in terms of levels of self-esteem.